THE PERFORMANCE OF EDUCATORS IN IMPROVING THE QUALITY OF LEARNING AT SMP NEGERI 6 NEGERI PANYABUNGAN - Afridah Afridah (Sean Institute, 2022)
This study aims to determine the quality of the performance of teaching staff in improving the quality of education at SMP Negeri 6 Panyabungan and to find out what factors influence teacher performance in improving the quality of education at SMP Negeri 6 Panyabungan. This type of research is qualitative research with a phenomenological approach , while type of research is descriptive.data collection techniques used observation techniques,Interview,and Documentation The informants used in this study totaled 15 teaching staff and were determined using the theory from John Minner in Sudarmanto's quote (2009: 11) namely the performance of teachers or educators from the results of the study showed that based on the 4 indicators in the study, the It can be concluded that the performance of educators in improving the quality of education at Panyabungan Public Middle School is: the time a teacher enters class to provide subject matter, as well as the ability of a teacher to use technology in learning media. Based on the results of the research conducted, the inhibiting factor for the performance of educators in improving the quality of education at SMP Negeri Panyabungan is the regulation of the Minister of National Education of the Republic of Indonesia number 16 of 2007 concerning academic qualification standards for teacher competency and work experience.